An Investigation of Exemplary ICT Integration: Enablers and Inhibitors of Best Practice in New South Wales Schools - Harrison, Colin Robert (Curtin University, 2017)
This study sought to determine the principles and practices common to exemplary teachers effectively integrating ICT in the secondary science and mathematics classrooms. Based on educator self-assessment of ICT integration level, several inhibitors and enablers of effective ICT integration were identified, most significantly high personal self-efficacy. Future professional learning may target the establishment of collegiate support groups, activities which promote student autonomy and the provision of time to support exemplary practitioners.